Improving 8th-grade students’ problem-solving skills and self-efficacy in probability using discovery learning - Hartiana, Wa Ode; Andriyani, Andriyani (Universitas Ahmad Dahlan, 2022)
This study aims to improve students' problem-solving skills and self-efficacy with the discovery learning model on the probability material for grade of VIII SMP. This type of research is classroom action research which is carried out in two cycles, with each cycle consisting of planning, action, observation and reflection stages. The subjects of this research were 32 students from grades of VIII. Data collection was used using questionnaires, observation and test techniques. Research data were analyzed through data reduction, data presentation and conclusion. Based on the study's results, it is known that implementing the discovery learning model can improve students' problem-solving skills and self-efficacy. This can be seen from the increase in the average score of students in the first cycle, which is 71 to 76.66 in the second cycle. The percentage of completeness in the first cycle also increased from 78% to 90% in the second cycle. This increase was also accompanied by an improved student self-efficacy from the percentage of 43.75% of students with high minimum criteria in cycle 1 to 66% in cycle II.